COMPARATIVE ANALYSIS OF MOTOR AND EMOTIONAL BEHAVIORAL DISORDERS IN CONDITIONS OF EXPERIMENTAL CHRONIC ISCHEMIC AND CHRONIC CONVULSIVE SYNDROMES - Vastyanov, R.S.; Kirchev, V.V.; Muratova, T.M.; Kashchenko, O.A.; Vastyanova, O.V.; Tatarko, S.V.; Zayats, L.M. (World of Medicine and Biology, 2021)
Chronic cerebral ischemia is a phenomenon and pathological process, and, accordingly, patients with chronic cerebral ischemia represent the vast majority of cases and episodes of cerebrovascular pathology. With chronic cerebral ischemia, the regulatory processes in the brain are significantly disrupted, the course of which is provided by vestibular, visual, cutaneous, proprioceptive and other sensory cortical projections and central control. The aim of the work is to determine in a comparative aspect the rat’s types of motor and emotional behavior disorders in the dynamics of both chronic cerebral ischemia and Kindling-induced chronic convulsive activity. The data obtained indicate that rats with a model of chronic ischemia already during the 1st day of the experiment revealed the expressed changes in motor and postural behavior, muscle and coordination activity, as well as severe neurological and emotional disorders. The obtained results of motor and emotional types of behavior changes in rats under conditions of chronic cerebral ischemia coincided with the results of similar types of behavior testing in rats with picrotoxin kindling. We consider the identity of the registered indexes in conditions of ischemic and convulsive brain damage to be fundamentally important, which testifies the common pathogenetic mechanisms of chronic cerebral ischemia and kindlind-induced chronic convulsive syndrome. The authors believed that a comprehensive pathogenetically based pharmacological correction of motor behavior and emotional sphere will result in anti-ischemic and anticonvulsant effects achievement.
Keywords: chronic cerebral ischemia; chronic convulsive syndrome; kindling; motor and emotional behavior disorders; pathogenetic mechanisms; complex pathogenetically based pharmacological correction